Clusters and local development: the case of the textile district of Atuntaqui - Paredes, César (2013)
Atuntaqui is heralded as a local economic development success story. The author scrutinizes the experience of the textile industrial district in Atuntaqui in the province of Imbabura, and concludes that the district actually represents a case of overspecialization, given a lack of economic diversification. Moreover the author notes that the municipality has an urban bias, pointing out the need for a broader ¨territorial¨ approach to local and regional development planning that factors in issues like water scarcity, rural poverty and exploitation of female labour, as opposed to the current myopic view that ignores rural urban linkages. In the article the success story of Atuntaqui is downplayed, stating that donors exaggerated the economic impact of the textile cluster.Atuntaqui is viewed as a model by neighboring cities as a result of its recent economic dynamism. Local policy makers need to look deeper into these efforts, and also take into account negative externalities, concluding that clusters are not a panacea for quick industrial development.